2010
DOI: 10.1002/mame.200900135
|View full text |Cite
|
Sign up to set email alerts
|

ZnO‐Based UV Nanocomposites for Wood Coatings in Outdoor Applications

Abstract: Nanocomposite UV coatings with adjustable properties for use on wood substrates in outdoor conditions were developed. Nanoscale ZnO was shown to be an efficient light absorber. Coatings were characterized in terms of elongation at brake, residual PI and double bond conversion, universal hardness, transparency, hydrophobicity, and yellowing. Coated samples were artificially weathered and studied with regard to their optical and mechanical properties, as well as to changes in brightness, transparency, hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 10 publications
0
40
1
Order By: Relevance
“…They observed no synergy between the particles and a HALS on coating performance [64]. Weichelt and co-workers found that spruce wood samples finished with clear coatings containing zinc oxide nanoparticles were less discoloured after accelerated weathering than samples finished with an unmodified coating [65]. The effectiveness of the modified coating at reducing discoloration was further enhanced if the wood was pre-treated with an organic "lignin stabilizer" [65].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed no synergy between the particles and a HALS on coating performance [64]. Weichelt and co-workers found that spruce wood samples finished with clear coatings containing zinc oxide nanoparticles were less discoloured after accelerated weathering than samples finished with an unmodified coating [65]. The effectiveness of the modified coating at reducing discoloration was further enhanced if the wood was pre-treated with an organic "lignin stabilizer" [65].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
“…Weichelt and co-workers found that spruce wood samples finished with clear coatings containing zinc oxide nanoparticles were less discoloured after accelerated weathering than samples finished with an unmodified coating [65]. The effectiveness of the modified coating at reducing discoloration was further enhanced if the wood was pre-treated with an organic "lignin stabilizer" [65]. Similarly, Cristea and Riedl showed that zinc oxide and titanium dioxide nanoparticles improved the durability of clear coatings on black spruce wood exposed to accelerated weathering [66].…”
Section: Inorganic Photostabilizersmentioning
confidence: 99%
“…However, hydrophobic coatings only prevent damage caused by water and do not protect the underlying wood against UV and visible (VIS) spectra causing decomposition of lignin and extractives [28,29], and they are associated with chemical and colour changes [30,31]. For wood stabilization, it is possible to use protective pigments which are used as parts of coatings [25], as well as nanoparticles [32][33][34][35], UV stabilizers [36], and HALS applied in the penetration protective layer [37][38][39]. Changes in the colour of surface layers due to the weathering process [40] and the effects of microscopic fungi [41][42][43] are observed on wood [44,45] and on the protective coatings [46,47] on its exterior.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are water-based coatings (varnishes and opaque paints) usually carrying organic or inorganic UV absorbers and radical scavengers. Studies on the UV protection efficiency of these combined products consisting of inorganic UV absorbers (ZnO, TiO2, CeO2) and a transparent coating such as water-based acrylic systems or maleic anhydride modified polypropylene or polyurethane were reported in several studies (9, 10,11,12,13). An addition of nano-fibrillated cellulose for carrying and homogenously distributing of UV absorbers for wood coatings was reported by Grüneberger et al (14,15).…”
Section: Introductionmentioning
confidence: 99%